Knowledge of Cardiovascular Disease and its Association Among General Population in Indonesia - Bella Anggelina; Susi Ari Kristina; Chairun Wiedyaningsih (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2023)
Knowledge of cardiovascular disease is essential for providing information about healthy behavior and to be proactive in reducing modifiable risk factors, control prevention, and improving early recognition. The existing study about knowledge of CVD in Indonesia is still limited. Hence, this study aimed to describe knowledge of CVD among general population in Indonesia and its association. A cross-sectional survey was conducted in 34 provinces in Indonesia from November-December 2021. Data were retrieved using a self-administered questionnaire. The Chi-Square analysis was performed to determine the association that contributes to overall knowledge of CVD. Among the 694 participants, 32.1% originated from Java, with the median age was 24 years and dominated by women (72.5%). The mean score of overall CVD knowledge was 59.6%, and only 39.1% of the participants had good knowledge of CVD. Cerebrovascular disease (94.7%) was the most identified various type of CVD. Likewise, unhealthy diet (77.2%), obesity (74.6%), and lack of exercise (72.5%) were the most identified risk factors. More than 50% of the participants recognized heart attack symptoms such as chest pain (77.1%) and shortness of breath (66.1%). Meanwhile, numbness or weakness (84.7%), trouble speaking (76.9%), and loss of balance (72.3%) were recognized as stroke symptoms. Gender, age, education level, working status, healthy food, smoking status, family history of CVD, ever checked blood pressure, fasting blood glucose, and total cholesterol were associated with overall knowledge of CVD. The disparity between level of CVD knowledge is not prominent among general population in Indonesia and further study need to establish.